Pemanfaatan Teknologi Asistif dalam Proses Pembelajaran Siswa dengan Hambatan Penglihatan - Zykra Zakiah; Veroyunita Umar; Muhammad Nurrohman Jauhari; Muchamad Irvan (Departement of Mathematics Education, 2024)
Assistive technology is present as a potential solution to overcome learning barriers faced by students with visual impairments. This study aims to examine the use of assistive technology in the learning process of students with visual impairments at elementary and secondary school levels. The method used in this study is a literature review. This study uses a content analysis approach from literature and journal articles that contain information about the use of assistive technology in the learning process of students with visual impairments. The literature was identified using keywords, years, and open access articles. The quality of this study adopts three stages, namely currency, conducting, reporting. Data sources for comprehensive research design were taken from articles containing research findings on the use of assistive technology in inclusive learning processes from three main sources, namely Science Direct, Google Scholar and Sage. The results of the study show that assistive technology has an important role in increasing accessibility, participation, and student learning achievement. Some types of assistive technology that are often used include screen reader software, braille displays, and mobility aids. However, there are still several challenges in the use of assistive technology in learning for students with visual impairments such as limited access to technology, lack of teacher understanding in implementing assistive technology in the learning process, and lack of support from the school environment.